ответ:1) (5а+3)+(-3а-4)=5а+3-3а-4=2а-1
(5а+ 3)-(-3а-4)=5а+3+3а+4=8а+7
2) (7х2+3х)+(-2х-1)=7х2+3х-2х-1=7х2+ 1х-1
(7х2+3х)-(-2х-1)= 7х2+3х+2х+1=7х2+ 5х+1
3)( 8b2 + 2b - 4)+( 5 - 3b - 9b2)= 8b2 + 2b – 4+5 - 3b - 9b2=-b2-b+1
( 8b2 + 2b - 4)-( 5 - 3b - 9b2)= 8b2 + 2b – 4 -5+3b+9b2=17b2+ 5b-9
4) (11y - 12 - y3)+( 14 - 12y + y3)= 11y - 12 - y3+14 - 12y + y3=-y+y3+2
(11y - 12 - y3)-( 14 - 12y + y3)= 11y - 12 - y3-14+12y-y3=23y-2y3-26
5) (6 + mn + 2)+( 4 - mn - m2)= 6 + mn + 2+4 - mn - m2=12-mn-m2
(6 + mn + 2)-( 4 - mn - m2)= 6 + mn + 2-4+mn+m2=4+2mn+m2
Объяснение:
не благодарите
(1+cos2x)/2 +(1+cos2y)/2 -(1-cos2(x+y))/2 = 2cosx ;
1+cos2x +1+cos2y -1+cos2(x+y) = 4cosx ;
(1+cos2(x+y) ) +(cos2x +cos2y )= 4cosx ;
2cos²(x+y) +2cos(x+y)cos(x-y) = 4cosx ;
2cos(x+y)( cos(x+y)+cos(x-y)) = 4cosx ;
2cos(x+y)*2 cosx*cosy = 4cosx ;
4cosx (cos(x+y)cosy -1) =0 ;
а) cosx =0 ;
x =π/2 +πk , k∈Z .
б) cos(x+y)cosy -1 =0 ⇔ cos(x+y)cosy=1 .
б₁) {cos(x+y) = -1 ; cosy= -1.
{ x+y =π+2πk ; y = π+2πn ⇒{x=2π(k -n) ; y = π+2πn .
б₂) {cos(x+y) =1 ; cosy= 1 ;
{x+y =2πk ; y = 2πn ⇒{x=2π(k -n) ; y = 2πn .